2008
DOI: 10.1002/em.20372
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the mode of action framework for mutagenic carcinogens case study: Cyclophosphamide

Abstract: In response to the 2005 revised US Environmental Protection Agency (EPA) Cancer Guidelines, a Risk Assessment Forum's Technical Panel has devised a strategy in which genetic toxicology data combined with other information are assessed to determine whether a carcinogen operates through a mutagenic mode of action (MOA). This information is necessary for EPA to decide whether age-dependent adjustment factors (ADAFs) should be applied to the cancer risk assessment. A decision tree has been developed as a part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
3
24
0
1
Order By: Relevance
“…In internal exposure studies 6,8 12,14) and in external exposure studies, 9,13,22,23) CP was frequently used as a marker of occupational exposures because of its slight volatility, 16) human genotoxicity, 16,24) reproductive toxicity, 25) carcinogenity, 17) and ease of detection. 26,27) Among several reports on occupational CP exposures in healthcare workers, some showed the presence of CP in the urine samples of nurses and pharmacists, 6,8 14) while others did not.…”
Section: Discussionmentioning
confidence: 99%
“…In internal exposure studies 6,8 12,14) and in external exposure studies, 9,13,22,23) CP was frequently used as a marker of occupational exposures because of its slight volatility, 16) human genotoxicity, 16,24) reproductive toxicity, 25) carcinogenity, 17) and ease of detection. 26,27) Among several reports on occupational CP exposures in healthcare workers, some showed the presence of CP in the urine samples of nurses and pharmacists, 6,8 14) while others did not.…”
Section: Discussionmentioning
confidence: 99%
“…The most important concern regarding high CP doses is the drug's toxic effects on the tissues [27,28] . It has been reported that CP's toxic effect is mediated by the degradation of antioxidant defence systems by acrolein, which is formed by the metabolisation of CP, resulting in excessive production of free radicals [2,3] . In the present study, SLY and CUR, which have strong antioxidant characteristics, were chosen in order to make it possible to use CP in high doses.…”
Section: Discussionmentioning
confidence: 99%
“…CP is an alkylating agent widely used in cancer chemotherapy, and its cytotoxic effects are the result of chemically reactive metabolites that alkylate DNA and protein, producing cross-links [1,2] . The major limitation of using CP is injury to normal tissues, which gives rise to numerous side effects [25] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations